Ladies in arms: Women, guns, and feminisms in contemporary popular culture - Hiergeist, Teresa; Schäfer, Stefanie (transcript Verlag, 2024)
In contemporary popular culture, armed women take center stage - but how can they be read from a feminist perspective? How do films, comics, and TV series depict the newly fashionable gunwomen between objectification and feminist empowerment? The contributions to this volume ask this question from different vantage points in cultural and literary studies, film and visual culture studies, history, and art history. They examine military and civic gun cultures, the rediscovery of historical armed women and revolutionaries, cultural phenomena such as gangsta rap, narcocultura and US politics, Bollywood and French cinema, and distinct genres such as the graphic novel, the romance novel, or the German police procedural Tatort.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Feminism; Gun Culture; Popular Culture; Heroines; Literature; Film; Visual Art; Memoir; Gender; Culture; Gender Studies; American Studies; Literary Studies